2005
DOI: 10.1145/1076211.1076249
|View full text |Cite
|
Sign up to set email alerts
|

How university professors teach project management for information systems

Abstract: Determining where project management education fits into the overall curriculum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…The ACM's 2002 recommendations for Information Systems (IS) [2] include an entire course on project management. However, Reif and Mitri's survey [10] of over 200 IS professors found that the recommended learning units are typically only partially covered across an array of different courses. Just 25% of IS respondents reported that their university offers an entire course on software project management.…”
Section: Rationalementioning
confidence: 99%
“…The ACM's 2002 recommendations for Information Systems (IS) [2] include an entire course on project management. However, Reif and Mitri's survey [10] of over 200 IS professors found that the recommended learning units are typically only partially covered across an array of different courses. Just 25% of IS respondents reported that their university offers an entire course on software project management.…”
Section: Rationalementioning
confidence: 99%
“…These academic experiences alone are not sufficient for preparing Software Engineering students for productive careers [19]. Project managers require "a combination of technical, human resources, and management skills coupled with on-the-job experience" [22].…”
Section: Teaching the "Real World"mentioning
confidence: 99%
“…Dawson [9] has vividly summarized several of these skills and has discussed their simulation in software engineering coursework. Reif and Mitri [22] also draw the distinction between traditional classroom training and practical experience with "informal" knowledge. They postulate that senior managers "construct mental models for the project, problems, and opportunities under investigation.…”
Section: Teaching the "Real World"mentioning
confidence: 99%
“…The need to reexamine how project managers are educated and trained cannot be overemphasized in light of emergent scholarship in the area of project management pedagogy (Atkinson, 2008; Berggren & Söderlund, 2008; Reif & Mitri, 2005; Rodriguez, Sicilia, Cuadrado‐Gallego, & Pfahl, 2006; Wearne, 2008). One such area, which appears to have been a focus of interest of scholars, has been in the area of the experiences of project management students (Ojiako, Chipulu, Ashleigh, & Maguire, in press) and, in particular, how virtual learning environments (VLEs) impact on this experience (Del Corso, Ovcin, & Morrone, 2005; Friedman & Deek, 2003; Hingorani, Sankar, & Kramer, 1998; Regueras, Verdu, Munoz, Perez, de Castro, & Verdu, 2009; Rodriguez et al, 2006).…”
Section: Introductionmentioning
confidence: 99%